Optimalisasi Pelayanan Pos Upaya Keselamatan Kerja (UKK) Kapal Sanggat di Pelayangan Kota Jambi - Faridah, Faridah; Hasmar, Wanti (Jurnal Abdimas Kesehatan (JAK), 2024)
Community empowerment in informal worker groups is work safety Post,which is a preventive measure to protect workers so they live healthy lives and are free from health problems and bad influences caused by work. Based on information from occupational health program holders at the  Tahtul Yaman Public health center, in 2020 the “Kapal Sanggat” work safety Post was formed, but the form of activity is only general in nature and carried out based on patient needs. In 2023, the Kapal Sanggat work safety already implemented innovation in the form of services for musculoskeletal disorders for batik workers. This community service aims to optimize Health Business Post services, increase cadres' knowledge about the health of batik workers. Problem solving solutions in this activity are realized by efforts to increase knowledge and understanding of the roles and functions of cadres. Method The activity was carried out by promoting health using counseling techniques and creating health promotion media in the form of leaflets and videos involving Health Business Post cadres. The instruments used were pre-test and post-test sheets. Then analyzed using frequency distribution for pre-test and post-test scores. The output target produced in this community service activity is the publication of an accredited journal. The results achieved were the implementation of the Health Business Post service and increased knowledge of cadres in implementing the "Kapal Sanggat" Health Business Post service